The Influence of Social Media on Increasing Sales of MSMEs (Case Study of MSMEs in Tanjung Morawa) - Sinaga, Mulyati Patresia; Kabeakan, Siat Putri; Damanik, Yogi Prasetya; Khaira, Imamul; Siregar, Zulkarnain (Lembaga Riset Mutiara Akbar (LARISMA), 2024)
Sales increase is the process of increasing the number of products or services sold by a company or individual in a certain time period. The goal is to increase revenue and profitability. Increased sales can be achieved through various strategies, including more effective marketing, improving product or service quality, expansion market, increasing distribution, improving customer service, and so on. The aim of this research is to determine the magnitude of the influence of social media on increasing sales of MSMEs in Tanjung Morawa. The results of this research show that social media has a positive and significant effect on increasing sales of MSMEs in Tanjung Morawa. The magnitude of the influence can be seen from the large value of the coefficient of determination (R square of 61.5%.)